2019
DOI: 10.1161/hypertensionaha.119.12703
|View full text |Cite
|
Sign up to set email alerts
|

Strong and Sustained Antihypertensive Effect of Small Interfering RNA Targeting Liver Angiotensinogen

Abstract: Small interfering RNAs (siRNAs) targeting hepatic angiotensinogen ( Agt ) may provide long-lasting antihypertensive effects, but the optimal approach remains unclear. Here, we assessed the efficacy of a novel AGT siRNA in spontaneously hypertensive rats. Rats were treated with vehicle, siRNA (10 mg/kg fortnightly; subcutaneous), valsartan (31 mg/kg per day; oral), captopril (100 mg/kg per day; oral), valsartan+siRNA, or captopril+valsartan for 4 weeks (all groups, n=8). Mean arterial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 39 publications
8
87
0
1
Order By: Relevance
“…Even though an increase in AGT mRNA was observed in the organoids, AGT protein was not detected in the supernatants. A recent publication demonstrated that liver-targeted AGT siRNA decreases AGT and angiotensin I protein levels in the kidney without affecting renal AGT mRNA expression 24 . Renal angiotensin generation is therefore considered to depend on the uptake of hepatic angiotensinogen.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Even though an increase in AGT mRNA was observed in the organoids, AGT protein was not detected in the supernatants. A recent publication demonstrated that liver-targeted AGT siRNA decreases AGT and angiotensin I protein levels in the kidney without affecting renal AGT mRNA expression 24 . Renal angiotensin generation is therefore considered to depend on the uptake of hepatic angiotensinogen.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In rats, both GalNAc-conjugated and unconjugated angiotensinogen ASO suppressed circulating angiotensinogen, although only the unconjugated ASO additionally suppressed renal and adipose angiotensinogen mRNA. Nevertheless, both the GalNAc-conjugated ASO and siRNA effectively lowered blood pressure in SHRs (Mullick et al, 2017; Uijl et al, 2019), suggesting that interference with renal or adipose angiotensinogen is not required for this effect. This was also true for lipid nanoparticle-encapsulated angiotensinogen siRNA delivered to the liver in SHRs (Olearczyk et al, 2014).…”
Section: Targeting Angiotensinogen: Antisense Oligonucleotides Anmentioning
confidence: 99%
“…Expectedly, either ASO or RNA-based therapies targeting AGT exerts similar effects as classical blockers of RAS (ACEI or ARB) on cardiac hypertrophy. It has been demonstrated that rats injected with liver-specific AGT siRNA or AAV AGT shRNA exhibit a profound reduction of ratio of heart weight to body weight (Kimura et al, 2001;Uijl et al, 2019).…”
Section: Pharmacological Manipulations Of Agt In Rodentsmentioning
confidence: 99%